Impact of adaptive cardiac resynchronization therapy in patients with systolic heart failure: Beyond QRS duration and morphology. Issue 3 (March 2022) - Fukata, Mitsuhiro; Yamasaki, Hiro; Sai, Eikou; Ogawa, Kojiro; Kuroki, Kenji; Igarashi, Miyako; Sekiguchi, Yukio; Kimura, Keizo; Seo, Yoshihiro; Odashiro, Keita; Akashi, Koich; Nogami, Akihiko; et al.
Abstract: Background: Mechanical and electrical restoration by cardiac resynchronization therapy (CRT) with adaptive pacing algorithm (aCRT) in heart failure patients with a moderately wide (120–149 ms) QRS has not been fully evaluated. The purpose of this study was to investigate the therapeutic effect of aCRT compared with conventional biventricular CRT (BiV-CRT) regardless of QRS morphology. Methods: Seventeen consecutive patients with a QRS ≥120 ms, regardless of morphology, underwent CRT device implantation with an aCRT pacing algorithm. Propensity score matched analysis was performed to evaluate the impact of aCRT on the improvement in mechanical and electrical parameters after CRT device implantation using historical controls (HC) from the clinical registry of BiV-CRT (START trial). Results: Left ventricular (LV) volume significantly decreased after CRT in all patients in both the aCRT and HC groups. The difference in relative reduction of LV end-systolic volume (LVESV) was not significantly different between the 2 arms. QRS shortening after CRT was significantly greater in the aCRT group than in the BiV-CRT group, and the difference was prominent in patients with a moderately wide QRS (120–149 ms). In patients with a moderately wide QRS, the relative reduction in LVESV [39 (29–47)% vs. 2 (−6–20)%, p  = 0.04] and proportion of LV volume responders (90% vs. 38%, p  = 0.04) were significantly greater in the aCRT group than in the HC group. The proportion of volume responders was not significantly different in patients with a wide QRS (≥150 ms). Conclusions: The aCRT algorithm improved electrical and mechanical parameters in patients with a moderately wide QRS, regardless of QRS morphology. Highlights: Cardiac resynchronization therapy (CRT) with adaptive pacing algorithm (aCRT) showed greater response than the echo-guided CRT in moderately wide QRS patients. QRS prolongation was not observed with aCRT in moderately wide QRS patients. The effect of aCRT was similar between patients with and without left bundle branch block. Abstract : Image, graphical abstract .